Transcriptional Changes in Pulmonary Phagocyte Subsets Dictate the Outcome Following Interaction With The Fungal Pathogen Cryptococcus neoformans - Hawkins, Ashlee N.; Determann, Brenden F.; Nelson, Benjamin N.; Wozniak, Karen L. (Frontiers in Immunology, 2021)
With over 220,000 cases and 180,000 deaths annually, Cryptococcus neoformans is the most common cause of fungal meningitis and a leading cause of death in HIV/AIDS patients in Sub-Saharan Africa. Either C. neoformans can be killed by innate airway phagocytes, or it can survive intracellularly. Pulmonary murine macrophage and dendritic cell (DC) subsets have been identified in the naïve lung, and we hypothesize that each subset has different interactions with C. neoformans. For these studies, we purified murine pulmonary macrophage and DC subsets from naïve mice – alveolar macrophages, Ly6c- and Ly6c+ monocyte-like macrophages, interstitial macrophages, CD11b+ and CD103+ DCs. With each subset, we examined cryptococcal association (binding/internalization), fungicidal activity, intracellular fungal morphology, cytokine secretion and transcriptional profiling in an ex vivo model using these pulmonary phagocyte subsets. Results showed that all subsets associate with C. neoformans, but only female Ly6c- monocyte-like macrophages significantly inhibited growth, while male CD11b+ DCs significantly enhanced fungal growth. In addition, cytokine analysis revealed that some subsets from female mice produced increased amounts of cytokines compared to their counterparts in male mice following exposure to C. neoformans. In addition, although cells were analyzed ex vivo without the influence of the lung microenviroment, we did not find evidence of phagocyte polarization following incubation with C. neoformans. Imaging flow cytometry showed differing ratios of cryptococcal morphologies, c-shaped or budding, depending on phagocyte subset. RNA sequencing analysis revealed the up- and down-regulation of many genes, from immunological pathways (including differential regulation of MHC class I in the antigen processing pathway and the cell adhesion pathway) and pathways relating to relating to metabolic activity (genes in the Cytochrome P450 family, genes related to actin binding, calcium voltage channels, serine proteases, and phospholipases). Future studies gaining a more in-depth understanding on the functionality of individual genes and pathways specific to permissive and non-permissive pulmonary phagocytes will allow identification of key targets when developing therapeutic strategies to prevent cryptococcal meningitis.